GraceKennedy Group: The new Chief Information Officer and IT Governance. Issue 2 (November 2019) - Golding, Paul; Facey-Shaw, Lisa
Grace Kennedy Group was the fourth largest Jamaican company listed on the Jamaican Stock Exchange by market capitalization in 2016. The company operated in several market segments focusing mainly on foods and financial services industries. Geographically, GraceKennedy Group had a diversified revenue stream operating across the Caribbean, Central and North America, Europe and Africa. Diversification had led to a diverse set of Information Technology platforms to serve the needs of the various subsidiaries of GraceKennedy Group. With the emergence of new technological trends like big data, social and cloud computing, the Group's Audit Committee in 2014 conducted a risk profile around the company's IT governance structure. The Committee recommended a change in the decentralized model of IT governance and the hiring of a Chief Information Officer to inter alia, strategically using IT to create value and to coordinate system security. The Chief Information Officer position was externally advertised; however, after several interviews, the Chief Executive Officer decided to offer the position to Robert Sutherland the then general manager of one of its subsidiaries. Sutherland was a former chairman of the Business Technology (BizTech) Council which was established in 2006 to oversee the delivery of IT services within the group and to provide guidance to the business leadership on enterprise-wide related matters such as the strategic use of IT. The case focuses on the issues faced by a newly promoted Chief Information Officer, in an environment in which the Chief Executive Officer has articulated the need for a new, transformative, strategic and value creating vision for IT.